Analysis of the effect of fermentation duration on the organoleptic properties of dried cocoa beans (Theobroma cacao L.) at Nglanggeran Agricultural Technology Park - Permata, Annisa; Hidayah, Nurul (Universitas Ahmad Dahlan, 2024)
The post-harvest process of cocoa fruits includes fruit harvesting, cracking, wet bean sorting, fermentation, drying, dry bean sorting, and packaging. One of the post-harvest processes that significantly affects the quality of cocoa beans is fermentation. The fermentation process, facilitated by acetic acid and lactic acid bacteria, aims to reduce moisture content, enhance aroma and flavor, and improve the quality of cocoa beans. Acetic acid bacteria, such as Acetobacter and Gluconobacter, contribute to acetic acid production, giving cocoa beans their characteristic flavor. These bacteria convert alcohol into acetic acid, a process crucial for developing the beans' flavor. On the other hand, lactic acid bacteria, like Lactobacillus and Pediococcus, play a role in the breakdown of complex compounds, enhancing the aroma. These bacteria produce lactic acid, which contributes to the beans' aroma. One factor that influences the success of cocoa fruit fermentation is the duration of fermentation. The optimal fermentation time for cocoa fruits is 5 – 6 days. If it is less or exceeds the optimal time, the fermentation of cocoa fruits will not be perfect. The duration of cocoa fruit fermentation has been proven to affect the aroma, taste, texture, and color of dried cocoa beans. Keywords: Cocoa, Fermentation, Post-harvest process of cocoa, Organoleptic